Variational and boundary value problems with perturbations - Walczak, Stanisław (Topological Methods in Nonlinear Analysis, 2001)
In the paper an optimization problem with parameters is considered. Somesufficient conditions under which the solutions of the problem continuoslydepend on parameters (in the weak or the strong topology of a Banach space)are proved. Moreover, some applications to the eigenvalue and boundary valueproblems for differential operators are given.